Impact of Rashtriya San Vikas Yojana on Rural Poverty and Vulnerability: A Case Study of South 24 Parganas, West Bengal. - Biswajit Chatterjee and Kundu. Sangeeta (2010)
This paper attempts to evaluate the impact of Rashtriya Sam Vikas Yojana (RSVY) programme in the district of South 24 Paraganas on the incidence of rural poverty and vulnerability among the targeted beneficiaries of the programme during 2003-06. The RSVY scheme aimed to promote focused developmental programmes for backward areas in the district so as to help reduce regional imbalances, speed up development and help backward areas to overcome poverty To gauge the extent of vulnerability of poor BPL rural households, the paper takes the Fuzzy measure of vulnerability as per multiple indicators of livelihood of the sample households in the district both before and after the introduction of the RSVY schemes. Although there have been indications of decline in the incidence of poverty across these chosen households after the RSVY programme is completed in terms of income criteria alone, the extent of vulnerability as measured by multiple criteria of deprivation chosen for these selected households do not indicate substantial diminution .